Field Study of Morphological Parameters in Step-Pool Streams - Torbizadeh, Abbas; Tahershamsi, Ahmad; Majdzadeh Tabatabai, Mohammad Reza (Civil Engineering Journal, 2018)
Nowadays, step-pool formations have attracted a lot of attention, which are distinguished by the successive arrangements of the bed, suitable geometry, and the tumbling flow pattern, which can highly disperse water energy. Field study of a stepâpool channel, along with one of the upper reaches of Kamandan River indicated a strong correlation between several morphological parameters of the river such as reach slope, step length, step height, pool depth, local slope, and the like. The length of the reach under the study is 145 meters and has an intermediate morphology based on Montgomery and Buffingtonâs classification. Therefore, twelve distinct step units were identified for 145 meters upstream while the rest was formed by steep morphology. In the present study, different definitions of wave length were applied to establish the relationships among the above parameters. For instance, the difference between apexes of every two successive step elevation was found to have a considerable relationship with the wavelength with a determination coefficient of 0.9. In addition, bankfull width and depth, along the profile for different cross-sections, were determined to establish a relationship between these parameters and pool spacing. Further, the parameters were applied to create a relationship with step heights.